BILE ACID MALABSORPTION: A REVIEW OF SEHCAT TESTING IN BELFAST. (8th June 2013) - Gray, J A; Robinson, M
Abstract : Introduction: Bile acid malabsorption (BAM) is a recognised cause of diarrhoea. Failure of bile acid absorption in the terminal ileum leads to excess bile in the colon causing diarrhoea due to a water and electrolyte secretion imbalance. SeHCAT testing is the current method of diagnosis of BAM. Current treatments available include cholestyramine, colestipiol and colevesalem. Aims/Background: The aims of this study were to review over a three year period the frequency and indications for SeHCAT testing and to assess the prevalence of type II BAM in those with idiopathic chronic diarrhoea and diarrhoea predominant irritable bowel syndrome (IBS-D). Method: A retrospective study was performed by reviewing both radiology records of SeHCAT tests and an electronic patient database. Results: A total of 61 studies were performed over a 3 year period: 8 (2010), 13 (2011) and 40 (2012). Female to male ratio was 2:1 (41:20). 52.5% (32) of tests performed were positive (retention rate <15%). The indication for testing was Chronic diarrhoea/IBS-D 40 (65.4%), inactive Crohns disease (with or without previous TI resection) 6 (9.8%), Post cholecystectomy 11(18%) and miscellaneous 4 (6.6%). Positive results by grouping were - Crohns disease 83.3% (3 severe, 1 moderate, 1 mild), post cholecystectomy 72.7% (4 severe, 4 moderate) and chronic diarrhoea/IBS-D 40% (9 severe, 4 moderate, 3 mild). Conclusion: The use of SeHCAT testing in the assessment of chronic diarrhoea while remaining under utilised is increasing. BAM is prevalent in those with chronic diarrhoea/IBS-D and where found represents a potentially treatable condition.